2020
DOI: 10.1177/2332858420901495
|View full text |Cite
|
Sign up to set email alerts
|

Instruction Quality or Working Condition? The Effects of Part-Time Faculty on Student Academic Outcomes in Community College Introductory Courses

Abstract: More than half of community college courses are taught by part-time faculty. Drawing on data from six community colleges, this study estimates the effects of part-time faculty versus full-time faculty on students’ current and subsequent course outcomes in developmental and gateway courses, using course fixed effects and propensity score matching to minimize bias arising from student self-sorting across and within courses. We find that part-time faculty have negative effects on student subsequent enrollments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Several studies show that when compared to students taught by full‐time faculty, students taught by adjunct faculty have similar or better course outcomes (Xu, 2019). On the one hand, in the six colleges that were the focus of this project, students with part‐time instructors had slightly higher course grades in developmental and gateway math and English courses, and similar pass rates in the next course in the sequence, compared with students with similar individual characteristics taught by full‐time faculty in the same courses (Ran & Sanders, 2020). On the other hand, studies also show that students who were taught by adjunct faculty tend to have lower enrollment persistence and weaker longer‐term outcomes (Eagan & Jaeger, 2009; Ran & Xu, 2019; Yu et al., 2015).…”
Section: The Influence Of Adjunct Faculty On Student Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies show that when compared to students taught by full‐time faculty, students taught by adjunct faculty have similar or better course outcomes (Xu, 2019). On the one hand, in the six colleges that were the focus of this project, students with part‐time instructors had slightly higher course grades in developmental and gateway math and English courses, and similar pass rates in the next course in the sequence, compared with students with similar individual characteristics taught by full‐time faculty in the same courses (Ran & Sanders, 2020). On the other hand, studies also show that students who were taught by adjunct faculty tend to have lower enrollment persistence and weaker longer‐term outcomes (Eagan & Jaeger, 2009; Ran & Xu, 2019; Yu et al., 2015).…”
Section: The Influence Of Adjunct Faculty On Student Outcomesmentioning
confidence: 99%
“…This finding aligns with the outcomes at the six colleges in this study. We found that students taught by part‐time faculty in developmental or gateway math and English courses were 3 to 5 percentage points less likely to enroll in a subsequent course in the sequence (Ran & Sanders, 2020).…”
Section: The Influence Of Adjunct Faculty On Student Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some of the working condition characteristics may directly affect faculty's capacity to engage students and, consequently, to positively impact student academic outcomes. A large volume of qualitative studies have identified a lack of institutional support and engagement for non-tenure-track faculty, where they often are not invited to departmental meetings, are excluded from curricular decision-making and planning, receive limited professional training opportunities and mentoring, and receive insufficient information on available student academic and nonacademic support services (e.g., Hoyt, 2012;Kezar, 2013;Kezar & Sam, 2013;Ran & Sanders, 2020;Schuster & Finkelstein, 2007). The working conditions are found to be particularly challenging for adjunct instructors hired in temporary part-time positions due to lack of office space, inadequate orientation, and insufficient time to prepare for the course (e.g., Eagan et al, 2015;Ran & Sanders, 2020).…”
Section: Variations In Working Conditionsmentioning
confidence: 99%